2 sin x – cos x =1
2sin x/2 * cos x/2 – cos² x/2 +sin² x/2 = sin² x/2 + cos² x/2
2sin x/2 * cos x/2 – 2cos² x/2 = 0
2cos x/2 * (sin x/2 – cos x/2) =0
cos x/2 * (sin x/2 – cos x/2) =0
cos x/2 = 0 или sin x/2 – cos x/2 = 0
cos x/2 = 0;
x/2 = π/2 + πk;
x = π + 2πk; k Є Z;
sin x/2 – cos x/2 = 0 – однородное уравнение первой степени.
Делим обе его части на cos x/2 (cos x/2≠ 0, так как,
если cos x/2 = 0, sin x/2 – 0 = 0 => sin x/2 = 0, что противоречит тождеству sin² x/2 + cos² x/2 = 1).
Получим tg x/2 – 1 = 0;
tg x/2 = 1;
x/2 = π/4 + πn;
x = π/2 + 2πn; n Є Z.
1) x = π + 2πk; k Є Z;
y = π/2 + π + 2πk; k Є Z;
y = π + 2πk; k Є Z;
(π + 2πk; k Є Z; π + 2πk; k Є Z;)
2) x = π/2 + 2πn; n Є Z.
y = π/2 + π/2 + 2πn; n Є Z.
y = π + 2πn; n Є Z.
(π + 2πk; k Є Z; π + 2πk; k Є Z)
ответ: (π + 2πk; k Є Z; π + 2πk; k Є Z) ;
(π + 2πk; k Є Z; π + 2πk; k Є Z)
где [cos²x=1-sin²x]
sin^4x-cos^4x=(sin²x-cos²x)*(sin²x+cos²x)=(sin²x-cos²x)*1=(sin²x-(1-sin²x)=sin²x+sin²x-1)=2sin^2x – 1
2sin^2x – 1 = – 0,7.